PENGARUH KESEIMBANGAN FOREMILK DAN HINDMILK DENGAN POLA DEFEKASI BAYI YANG MENDAPATKAN ASI EKSKLUSIF DI DESA SUKARENDE - Debora Paninsari; Latifah Nurhayati (Universitas Medan Area, 2019)
Mothers who exclusively breastfed their babies from 2011-2015 tended to increase. However, in breastfeeding there are still many maternal understandings that are lacking about foremilk and hindmilk. Foremilk and hindmilk are related to the duration of the baby breastfeeding, if the baby has not been obtained in a balanced manner can cause problems in the pattern of defecation of infants especially those aged 1-6 months. The purpose of study was to determine the effect of foremilk and hindmilk balance with defecation patterns of infants who received exclusive. The study design was cross sectional, with total sample 30 mothers who had infants aged 1-6 months and exclusively. The results showed the majority (96.7%) frequency of defecation of infants 1-8 times, consistency of soft stool (96.7%) and yellow stool (93.3%). Out of 30 respondents 53.33% of mothers had a balance of foremilk and hindmilk while breastfeeding and 86.66% of infants had normal defecation patterns. Chi-square test results did not influence the balance of foremilk and hindmilk with the pattern of defecation with 30 respondents surveyed. This shows that the balance of foremilk and hindmilk has not affected the pattern of infant defecation including frequency, consistency and color of feces.